Survival analysis of time to amputation following diabetic foot ulcer diagnosis among Indonesians - Lianawati; Wongsa Laohasiriwong; Kyaw Min Htike; Kavin Thinkhamrop; Roshan Kumar Mahato (PLoS ONE, 2026)
Background Diabetic foot ulcer (DFU) is a severe complication of diabetes that often leads to amputation and high mortality, yet survival outcomes and risk factors after DFU-related amputation remain poorly understood particularly in Indonesia. This study aims to determine the incidence rate (IR), survival rate and to identify factors associated with the survival of amputation among patients having DFU in Indonesia. Methods This retrospective cohort study included Type 2 Diabetes Mellitus (T2DM) patients with DFU admitted to the Margono Hospital in Central Java Indonesia. The primary outcome of this study was the times since diagnosis of DFU to amputation. This study outcome was conducted for 5-year survival (2019–2024), IR and survival rate of amputation. Multiple cox regression was performed to investigate factors associated with survival, quantified by adjusted hazard ratios (AHR) and their 95% CIs. Results This cohort comprised 878 DFU patients and followed up for 1,350.55 person-year within the study period. The overall amputation IR was 14.22 per 100 person-year (95% CI: 12.34–16.38) with the highest IR/100 population was 85.68 (95% CI: 73.49–99.90) occurred in the gangrene group. The overall survival rate within 1-year, 3-year and 5-year was 76.14% (95%CI: 72.82–79.11), 72.77% (95%CI: 69.08–76.10) and 71.18% (95% CI: 67.22–74.75) respectively with the highest five-year survival rates were observed among patients with cardiovascular disease (94.37%, 95% CI: 85.17–97.93). Factors that were associated with survival included patients who receiving insulin therapy (AHR: 5.51; 95% CI: 3.73–8.14), residing in rural areas (AHR: 4.14; 95% CI: 1.70–10.12), patients without neuropathy (AHR: 2.40; 95% CI: 1.30–4.42), those with underweight or normal BMI (AHR: 2.04; 95% CI: 1.40–2.98), and those without hypertension (AHR: 1.52; 95% CI: 1.03–2.22). Conclusions The study revealed that the rate of amputations was relatively high and highest survival rate was patients with cardiovascular disease. Receiving insulin therapy, staying in rural area, no-neuropathy, underweight and normal weight and no-hypertension showed more likely to amputation. Early detection of comorbidities is recommended to prevent amputation among patients with DFU.